Young age and short duration of the disease are associated with more frequent relapses in inflammatory bowel disease patients - Nakov, Radislav; Nakov, Ventsislav (Medicine and Pharmacy Reports, 2021)
Aims. To evaluate the effects of the clinical predictors such as age, duration of disease, sex, and smoking on the frequency of relapses in IBD patients. Methods. This study recruited 289 IBD (133 with CD and 156 with UC) patients. All were followed-up for 36 months for relapses of the disease. We defined as frequently relapsing (≥1/year) patients with at least one relapse per year and as infrequently relapsing those with less than one relapse per year (<1/year). We assessed the effect of the clinical predictors: age, duration of disease, sex, and smoking on the frequency of relapses in IBD patients. Results. Sixty-four (48.1%) of the CD patients were frequently relapsing and 69 (51.9%) were infrequently relapsing. There was a significant association between the age and the frequency of relapse (p=0.001; OR 0.964; 95% CI 0.941-0.987, p=0,002) and between the duration of the disease and frequency of relapse (р<0.001; OR 0.740, 95% CI 0.655-0.837, p<0.001). Seventy-two (46.2%) of the UC patients were frequently relapsing and 84 (53.8%) were infrequently relapsing. There was a significant association between the age and the frequency of relapse (p=0.001; OR 0.964, 95% CI 0.941-0.987, p=0.002) and between the duration of the disease and frequency of relapse (р<0.001; OR 0.740, 95% CI 0.655-0.837, p<0,001). Conclusion. We demonstrate in a relatively significant cohort of IBD patients that young age and short duration of the disease are associated with more frequent relapses.